Dominasi Patriarki Dalam Tradisi Mendhak Sanggringan di Desa Tlemang Lamongan - Afifah, Fika Nur Aghni; Harianto, Budi (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This research examines the patriarchal dominance found in the Medhak Sanggring tradition in Tlemang Lamongan Village. Mendhak Sanggring is a tradition carried out to commemorate the death and graduation day of the village founder, Ki Buyut Terik. In its implementation, there are four traditional stages, namely sitting in the spring, cleaning the cungkup (grave), puppet performances and cooking goat meat, as well as cooking sanggring vegetables and visiting the grave. In practice, all stages are mostly carried out by men. Women are only assigned to strategic tasks such as cooking. This research uses descriptive qualitative methods with direct data collection techniques in the field, namely observation and interviews. The results of this research are that the people of Tlemang Village are not aware of the patriarchal culture contained in the Mendhak Sanggring tradition because the tradition has existed since before they were born. So the domination of men is always considered normal because the rules that have been applied since the past have been like that. Then, forms of male domination can be seen at every stage of the tradition, starting from forming a committee, sitting at the spring, cleaning the grave, to cooking sanggring vegetables.